PENTINGNYA PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS - Marsianus Meka; Oktaviani Meno; Rosadalma Bengu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out the literature about the importance of inclusive education for children with special needs. This type of research is literature review research which proves that inclusive education can overcome the social problems of children with special needs. This research method uses a descriptive qualitative research method with a literature review approach. Data collection was carried out by searching for articles and books from electronic journals, namely via Google Scholar, which can strengthen the analysis results.